Penguatan Kompetensi MSDM Mahasiswa melalui Experiential Learning Industri Pangan di PT Bakpia Juara Satoe - Duwi Laila Pitri; Femi octaviani; Juliyana Puspita Sari; Melvi Yansi (Rengganis Jurnal Pengabdian Masyarakat, 2026)
This community service activity represents an experiential learning approach that bridges academic theory with real industrial practice. This community service article presents the results of a service program conducted by students of the Management Study Program, Universitas Prof. Dr. Hazairin, SH. Bengkulu, at PT Bakpia Juara Satoe, Yogyakarta, on February 6, 2026. The activity involved 40 management students, with each Field Supervisor Lecturer accompanying 14 students. The program focused on observation and participation in the bakpia production process, examination of the human resource management (HRM) system, implementation of on-the-job training, mentoring systems, and the application of Personal Protective Equipment (PPE) standards in the food industry. The methods employed included participatory observation, structured interviews with company management representatives, and structured reflection. The results indicated that PT Bakpia Juara Satoe has implemented structured HRM practices, including selective recruitment, hands-on training, SOP standardization, and performance-based compensation systems. The consistent use of PPE reflects the internalization of a work culture oriented toward quality and food safety. Of the ten HRM aspects examined, seven aspects were found to align with theoretical standards, two aspects were partially implemented, and one aspect still requires further development. The activity was proven to enhance students' competencies and practical insights in the field of human resource management.